Strategy of human resources development in improving performance Apparatus in the Bone Regency Regional Inspectorate - Henni Zainal; Muhammad Rakib; Andi Idham Ashar; Darmawati Manda; Andi Tenry Sose; Ignasius Setitit (Pinisi Business Administration Review, 2020)
Human resources is an organization whose resources are the most important and can only be obtained through recruitment efforts. The purpose of this study was to determine the strategy of developing human resources in improving the performance of the apparatus in the Bone regional inspectorate. Research conducted with a qualitative approach with survey methods. Data collection techniques used were interviews and surveyors. The data analysis technique is data analysis in the research process is a very urgent factor because it is a stage that presents a series of information; objectively and rationally about the data or facts found in the field. The results showed that the strategy for developing human resources in the Regional Inspectorate of Bone Regency was through formal education. Where employees are given the opportunity to take part in education freely. The next strategy is employee training but training is not carried out periodically due to limited budget which causes limited training time as well.